Pengaruh Load Balancing Pada Ser Pengaruh Load Balancing Pada Serangan DDoS Menggunakan Nginx: Pengaruh Load Balancing Pada Serangan DDoS Menggunakan Nginx - Satrya Bhayangkara, Dimas; Miftahul Ashari, Wahid (AI Society & STMIK Indonesia, 2024)
DDoS (Distributed Denial of Service) attacks are one of the most common cyberattacks. This attack can make a server experience an error. Various methods have been used to overcome this attack, one of which is load balancing. Load balancing is responsible for dividing the workload among various servers evenly. In this study, we used Nginx load balancing. The research was conducted by sending 100000, 300000, 400000, and 500000 requests. Throughput after using load balancing shows superiority, with an average of 9,581 kb/s compared to not using load balancing. Response time using load balancing is also better than not using load balancing, with an average of 4507.23 ms. However, the packet loss shows no packet loss, which is 0% after using load balancing and before using load balancing. The effect of load balancing on Nginx can prevent DDoS attacks with a load balancing algorithm that is still good enough to use.